Kualitas Mikroba Produk Olahan Daging yang Dijual Secara Daring Dari UMKM di Kota Bandung - Maulidina, Rizka; Marlina, Eulis Tanti; Utama, Dicky Tri (Unpad Press, 2023)
Culinary is one of the choices of business fields that are in great demand by Micro, Small and Medium Enterprises (MSMEs) entrepreneurs in starting their business. E-commerce can be used by MSME entrepreneurs to distribute products to consumers in the digital transformation phase. The study was conducted to examine the microbiological quality of processed meat products sold online from the city of Bandung and sent throughout Indonesia. The research method used is descriptive with a non-experimental quantitative approach to describe the results of total bacterial analysis using the Total Plate Count (TPC) method and total coliform analysis using the Most Probable Number MPN) method. The sampling technique uses purposive sampling on Shopee and Tokopedia online sales media based on regular delivery methods. Samples of processed meat products in the form of meatballs and nuggets. The research data were analyzed using descriptive statistics which are mean, standard deviation and coefficient of variation. The results showed an average total number of bacteria in processed meat products in the form of meatballs as much as 2.10 x 10 10 CFU g and nuggets as much as 4.29 x 10⁷ CFU/g. The total number of meatball coliforms is 43 to >1100 MPN/g while nuggets are 1100 to >1100 MPN/g. The results obtained from this study showed that the total bacteria and coliforms in processed meat products exceeded the threshold specified in SNI 7388:2009, which are 10 5 cfu/g for total bacteria and 10 MPN/g for total coliform